Reservoir Simulation Model for the Design of Irrigation Projects - Madeti, S (Elsevier, 2022)
This chapter presents a simulation model for the optimization of a reservoir system that is being developed. Simulation studies were carried out, firstly to determine the best (and by how much) irrigation facilities to provide in the proposed new scheme, and secondly, to see the applicability of simulation in reservoir planning. A computer simulation model using MATLAB has been developed to analyze optimal reservoir capacity. A cost-benefit analysis is a systematic process to determine the payback. The operation model has been applied to Harabhangi single-purpose irrigation in Orissa State, India. From the simulation results, it is found that a lower capacity of 120MCM (million cubic meters) may only be required to satisfy the future annual irrigation requirement of 220MCM, whereas the existing reservoir capacity is already in excess. This study can be helpful to obtain maximum benefits of any reservoir system by optimal utilization of water resources. © 2022 Elsevier Inc. All rights reserved.